Differential modulation of phospholipase D and phosphatidate phosphohydrolase during aging in rat cerebral cortex synaptosomes - Salvador, Gabriela Alejandra (2002)
Phosphatidylcholine (PC) hydrolysis generates two important second messengers: phosphatidic acid (PA) and diacylglycerol (DAG). Phospholipase D (PLD) and phosphatidate phosphohydrolase (PAPase) are involved in their generation and therefore are key enzymes in signal transduction. Specific isoforms of these enzymes are activated by receptor occupancy in brain. Phosphatidylinositol 4,5-bisphosphate-dependent PLD (PIP2-PLD) and N-ethylmaleimide-insensitive PAPase (PAP2) have been suggested to act in series to generate the biologically active lipids PA and DAG. In the present study we examine age-induced changes mainly in PIP2-PLD and PAP2 activities in cerebrocortical synaptosomes from adult (4 months) and aged (28 months) Wistar rats. Aging increases the activity of both enzymes. Guanosine 5′-O-(3-thiotriphosphate) (GTPγS) and cytosol (from cerebral cortex) stimulate PLD activity in adult and senescent synaptosomal membranes, the effect being greater in the latter. Under the same experimental conditions PAP2 activity was stimulated in aged membranes whereas in adult membranes GTPγS had no effect and cytosol showed a slight inhibitory effect. Diacylglycerol lipase (DGL) activity differs from that of PAP2 in aged rats and it was 21% inhibited with respect to synaptosomal membranes from adult rats. Increased sinaptosomal PLD activity in aged membranes appears to be independent of G protein regulation, whereas PAP2 activity is differentially regulated by GTPγS in aged membranes with respect to adult membranes. Our results suggest that under G-protein activation conditions, DAG production by the serial activation of PLD and PAP2 activities is increased in synaptosomal membranes from aged brain. The present paper demonstrates that PA generation (PLD activity) and degradation (PAPase activity) are differentially modulated during the aging process.